- مقهي عكاظ - مكتبة ومقهى عصري - = Library and coffee shop (OkzdhCOS) - خويدمي, مصطفى; قعيش, بشرى (كلية الأدب العربي والفنون, 2024)
تناولت المذكرة دور النوادي الثقافية في تطوير اللغة العربيةوتعزيز الاستخدام السليم لها وصقل مهارات الكتابة والقراءة بين أفراد المجتمع. واستعرضت الدراسة أبرزمظاهر الثقافة في تاريخ العرب من منظور لغوي، كما تطرقت إلى وصف مشروع "مقهى عكاظ"من أهم جوانبهالفنية والاقتصادية ودوره فيخدمة اللغة العربية وأهم الخدمات التي يقدمها. وخُتمت المذكرة بتوصيات لتعزيز دور النوادي الأدبية في نشر ثقافة استخدام اللغة العربية بين أفراد المجتمعوتعزيز مكانتها بصفتها لغة حضارية وثقافية مهمة This study explores the role of cultural clubs in developing the Arabic language, promoting its proper usage, and refining writing and reading skills among community members. It discusses cultural aspects of Arab history from a linguistic perspective, along with an overview of the "Maktabah 'Ukaz" project, highlighting its artistic and economic dimensions and its service to the Arabic language. The paper concludes with recommendations to enhance the role of literary clubs in spreading the culture of Arabic language usage and strengthening its position as a significant cultural and civilizational language.
Keywords: Coffee shop-library- Promote the use of the Arabiclanguage- cultural clubs.; مقهى،مكتبة،تعزيز استعمال اللغة العربية، النوادي الثقافية.